Photocatalytic Performance Of ZnO Nanorod Coupled Photocatalysts Under Fluorescent Light And Sunlight Irradiation For Phenol And 2,4-Dichlorophenoxyacetic Acid Degradation - Lam, Sze Mun (2014)
Over the years, the surge of industrial activities that inevitably resulted in an increasing flux of pollutants in the environment still remains an intricate challenge for nations. Heterogeneous photocatalysis, particularly on metal oxide coupled on one dimensional (1D) ZnO nanorods (MOx/ZnO) as promising heterostructured photocatalysts were employed to treat two endocrine disrupting chemical (EDC) pollutants, namely phenol and 2,4-dichlorophenoxyacetic acid (2,4-D). Selama bertahun-tahun, aktiviti perindustrian yang pesat masih menjadi satu cabaran yang rumit bagi kebanyakan negara. Aktiviti perindustrian yang tidak dapat dielakkan ini menyebabkan peningkatan bahan pencemar ke dalam alam sekitar. Fotopemangkinan heterogen, terutamanya pada logam oksida digandingkan dengan satu dimensi (1D) ZnO berbentuk rod nano (MOx/ZnO) bertindak sebagai fotopemangkin heterostruktur yang berkesan telah digunakan untuk merawat dua bahan pencemar kimia pengganggu endokrin (EDC) iaitu fenol dan asid 2,4-diklorofenoxiasetik (2,4-D).